Applicability of Virtual Commissioning Concepts in Industrial Robotics as a Solution for Compatibility Issues Between Virtual Simulation and Logic Control Software - Alexandru Andrei; Florin-Adrian Nicolescu; Cristina Pupăză; Cezara-Georgia Coman; Ionuț Gabriel Ghionea (Applied Sciences)
This article presents the results of applied research focused on the development of a hybrid software solution, which is based on the ABB RobotStudio 2021 suite, because even in the latest version, RobotStudio 10 does not have a dedicated virtual commissioning module. The aim of the study is to explore the potential communication capabilities between ABB RobotStudio and Siemens Simatic Robot Integrator and to unify control systems for performing virtual commissioning tasks. The proposed solution offers valuable procedures for any end user responsible for implementing robotic cell virtual commissioning tasks and ensures the compatibility between hardware and software components from ABB and Siemens manufacturers integrated into any robotic cell type. Siemens, one of the leading PLC manufacturers, offers the complex PLM platform Process Simulate, which can be integrated with the Totally Integrated Automation (TIA) Portal and Mechatronics Concept Designer (MCD) for developing virtual commissioning (VC) applications. The TIA Portal is recognized by robotics application integrators as the most efficient work environment for VC. However, there is currently no direct compatibility between the ABB RobotStudio (RS) platform and Siemens TIA Portal. To address integration challenges, Siemens has introduced the Simatic Robot Integrator (SRI) platform, which ensures compatibility with certain proprietary software from various robot manufacturers, including KUKA, Motoman, and Staubli. While Siemens has collaborated with manufacturers like KUKA and Kawasaki, major industry manufacturers such as ABB and Fanuc have yet to establish a standardized interface within the Siemens SRI platform. A mathematical model was also developed, which serves as a key perspective and a valuable tool for the future integration of double-portal-type robots into the working environments of ABB and Siemens. This integration aims to facilitate virtual commissioning in scenarios where such robots need to be implemented. Currently, ABB’s library does not include double-portal-type robots, despite the fact that leading manufacturers of double-portal robot types utilize ABB’s IRC5 controllers.